The Australian labour market in 2020. (June 2021) - Birch, Elisa; Preston, Alison
This article provides a review of the Australian labour market in 2020. It outlines the monetary and fiscal responses to COVID-19 (including JobKeeper, JobSeeker and JobMaker policies), describes trends in employment, unemployment and underemployment and summarises the Fair Work Commission's 2020 minimum wage decision. Data show that in the year to September 2020, total monthly hours worked fell by 5.9% for males and 3.8% for females. Job loss was proportionately larger amongst young people (aged 20–29) and older people. It was also disproportionately higher in female-dominated sectors such as Accommodation and Food Services. Unlike the earlier recession (1991), when more than 90% of jobs lost were previously held by males, a significant share (around 40%) of the job loss in the 2020 recession (year to August 2020) were jobs previously held by females. Notwithstanding a pick-up in employment towards year's end, the future remains uncertain.